What Keeps Postpulmonary Resection Patients in Hospital? - T Bardell; D Petsikas (Canadian Respiratory Journal)
BACKGROUND: Prolonged air leak (longer than three days) was hypothesized to be the primary cause of extended hospital stays following pulmonary resection. Its effect on length of stay (LOS) was compared with that of suboptimal pain control, nausea and vomiting, and other causes. Predictors of prolonged LOS and of prolonged air leaks were investigated.